ICPMS analysis of proteins separated by Native-PAGE: Evaluation of metaloprotein profiles in human synovial fluid with acute and chronic arthritis - Moyano, Mario Franco (2016)
The role of trace elements bound to proteins in the etiology and pathogenesis of rheumatoid arthritis (RA) remains unclear. In this sense, the identification and detection of metalloproteins has a strong and growing interest. Metalloprotein studies are currently carried out by polyacrylamide gel electrophoresis (PAGE) associated to inductively coupled plasma mass spectrometry (ICPMS), and despite that complete information can be obtained for metals such as Fe, Cu and Zn, difficulties due to poor sensitivity for other trace elements such as Sn, As, etc, are currently faced. In the present work, a simple and fast method for the determination of trace metals bound to synovial fluid (SF) proteins was optimized. Proteins from SF (long and short-term RA) were separated in ten fractions by native PAGE, then dissolved in nitric acid and peroxide hydrogen, and analyzed by ICPMS. Fifteen metals were determined in each separated protein fraction (band). Adequate calibration of proteins molecular weight allowed stablishing which protein type were bound to different metals.